Clinical Indications Of Kamadudha Rasa A Scientific And Experiential Review - Shripathi, Acharya G; Acharya, Miss Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Herbomineral formulations are popularly used in the treatment by Ayurveda physicians . Arogyavardhini vati, Gandhaka Rasayana , Mrityunjaya rasa, Pravala panchamrita rasa, and Yogaraja guggulu are commonly used such preparations. Kamadudha rasa is one such preparation which is pittahara in action and given in pittaja disorders . Kamadudha rasa is having ingredients like pravala bhasma , mukta bhasma , mukta shukti bhasma , shankha bhasma , varatika bhasma , shuddha gairika and guduchi satva. All these ingredients are having sheeta virya and pittahara actions . They can be given in urodaha , udaradaha , amlapitta , parinama shoola , annadrava shoola and hyperacidity syndrome . These mainly contain mainly calcium and supplements it to the body tissues . The present paper highlights about the clinical indications of Kamadudha rasa in a scientific and experiential view.